2014
DOI: 10.1371/journal.pone.0096281
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mouse Embryonic Stem Cell Proliferation and Neural Differentiation by the P2X7 Receptor

Abstract: BackgroundNovel developmental functions have been attributed to the P2X7 receptor (P2X7R) including proliferation stimulation and neural differentiation. Mouse embryonic stem cells (ESC), induced with retinoic acid to neural differentiation, closely assemble processes occurring during neuroectodermal development of the early embryo.Principal FindingsP2X7R expression together with the pluripotency marker Oct-4 was highest in undifferentiated ESC. In undifferentiated cells, the P2X7R agonist Bz-ATP accelerated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 64 publications
5
53
1
2
Order By: Relevance
“…Similar hypothesis that neurogenesis contributes to worsen seizures was presented previously [86]. P2X7R have been shown to modulate mechanisms involved with apoptosis/necrosis and neuronal differentiation of NPCs [87][88][89][90], while P2Y1 receptors modulate proliferation and migration of NPCs [91][92][93]. Klaft et al [94] also found that P2X7R antagonists had a minor antiepileptic effect in medial entorhinal cortex on rats subjected to pilocarpine-induced epilepsy.…”
Section: Discussionsupporting
confidence: 64%
“…Similar hypothesis that neurogenesis contributes to worsen seizures was presented previously [86]. P2X7R have been shown to modulate mechanisms involved with apoptosis/necrosis and neuronal differentiation of NPCs [87][88][89][90], while P2Y1 receptors modulate proliferation and migration of NPCs [91][92][93]. Klaft et al [94] also found that P2X7R antagonists had a minor antiepileptic effect in medial entorhinal cortex on rats subjected to pilocarpine-induced epilepsy.…”
Section: Discussionsupporting
confidence: 64%
“…By the same token, increased levels of kinin receptor expression would not support previously observed inhibition of invasion of GBM cells in indirect interactions with MSC (9). With respect to the underlying mechanism, Montana and Sontheimer (16) showed that bradykinin via B2R-induced [Ca 21 ] i transients enhanced and directed invasion of glioma cells toward blood vessels. Moreover, Seifert and Sontheimer (15) recently revealed that bradykinin through [Ca 21 ] i transients in GBM cells in vitro induced the formation of small bleb-like protrusions at the plasma membrane, which stimulated an amoeboid phenotype of cell migration.…”
Section: Discussionmentioning
confidence: 73%
“…In this context, expression of transcription factors, such as Slug and Sox9, was demonstrated both in CSC and during EMT [108,109]. Purines, through P2X7 receptors, contribute to the maintenance of stemness in embryonic stem cells [110], and they regulate the proliferation rate of cancer stem cells and endothelial progenitors [111]. Further studies are needed to confirm and extend purinergic regulation in CSC biology.…”
Section: Adora2amentioning
confidence: 99%